CD40 Accelerates the Antigen-Specific Stem-Like Memory CD8+ T Cells Formation and Human Papilloma Virus (HPV)-Positive Tumor Eradication - Zhang, Yanmei; Wang, Nisha; Ding, Meilin; Yang, Yang; Wang, Zhimin; Huang, Lei; Zhu, Wei; Mellor, Andrew L.; Hou, Xiaorui; Zhou, Chenfei; Yan, Ruiming; Wang, Wei; et al. (Frontiers in Immunology, 2020)
Antigen-specific stem-like memory CD8+ T cells (Tscm) have a series of stem cell characteristics, including long-term survival, self-renewal, anti-apoptosis and persistent differentiation into cytotoxic T cells. The effective induction of tumor-specific CD8+ Tscm could persistently eradicate tumor in pro-tumor hostile microenvironment. This study was to investigate the role of CD40 in HPV16-specific CD8+ Tscm induction and its anti-tumor function. We found that CD40 activation accelerated vaccine-induced HPV16 E7-specific CD8+ Tscm formation. Comparing to other HPV-specific CD8+ T cells, CD8+ Tscm were found to be stronger and long-term anti-tumor function, in vivo and vitro, even in the adoptive cellular transferring model. Furthermore, high frequencies of Tscm might prevent the HPV infection to move on to the development of cancer. And the CD40 effect on Tscm involved Wnt/β-catenin activation. Our study suggest that CD40 activation supports the generation of tumor-specific CD8+ Tscm, thus providing new insight into cancer immunotherapy.